2019
DOI: 10.3847/1538-4365/aaf73d
|View full text |Cite
|
Sign up to set email alerts
|

The Ultraviolet Detection of Diffuse Gas in Galaxy Groups

Abstract: A small survey of the UV-absorbing gas in 12 low-z galaxy groups has been conducted using the Cosmic Origins Spectrograph (COS) on-board the Hubble Space Telescope (HST). Targets were selected from a large, homogeneously-selected sample of groups found in the Sloan Digital Sky Survey (SDSS). A critical selection criterion excluded sight lines that pass close (< 1.5 virial radii) to a group galaxy, to ensure absorber association with the group as a whole. to characterize these 10 13.5 to 10 14.5 M groups, the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 78 publications
4
12
0
Order By: Relevance
“…This may be an indication that we are not observing a hot, volume filling IGrM; instead we are detecting cooler pockets of gas that are perhaps in pressure confinement within the IGrM. This would line up more closely with what was concluded in Stocke et al (2017); Pointon et al (2017) and Stocke et al (2019) for more massive groups. If this is indeed correct, X-ray spectroscopy of O VII and O VIII would be required to observe the hotter component of the IGrM, even for lower mass groups (10 12.8 − 10 13.7 M ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This may be an indication that we are not observing a hot, volume filling IGrM; instead we are detecting cooler pockets of gas that are perhaps in pressure confinement within the IGrM. This would line up more closely with what was concluded in Stocke et al (2017); Pointon et al (2017) and Stocke et al (2019) for more massive groups. If this is indeed correct, X-ray spectroscopy of O VII and O VIII would be required to observe the hotter component of the IGrM, even for lower mass groups (10 12.8 − 10 13.7 M ).…”
Section: Discussionsupporting
confidence: 81%
“…The possibility that the O VI detections were tracing cooler clouds rather than the hot component of the IGrM was still a hypothesis and it lacked any direct observational confirmation. Other O VI studies by Pointon et al (2017) and Stocke et al (2017) compared the detections in group environments to the circumgalactic medium (CGM) of isolated galaxies. These studies found that group environments contained O VI absorption that could be modeled with broader components than isolated systems and concluded that O VI was characteristic of the boundary between cooler CGM gas and the hotter IGrM.…”
Section: Introductionmentioning
confidence: 99%
“…Since X-ray emission scales with the square of gas density, diffuse warm and cool phases of the IGrM are prohibitively difficult to observe directly in emission. While several groups have pioneered efforts to characterize the warm and cool IGrM/ICM with UV absorption specifically targeting group environments (Pointon et al, 2017;Nielsen et al, 2018;Stocke et al, 2019), the Virgo (Yoon et al, 2012;Manuwal et al, 2019) and Coma (Yoon & Putman, 2017) clusters, other clusters (Burchett et al, 2018;Connor et al, 2019), cluster outskirts (Muzahid et al, 2017;Pradeep et al, 2019), as well as low-mass group halos hosting ETGs (Zahedy et al, 2019), such studies are limited by the available number of background sources with existing instrument sensitivities. For this reason, simulations of groups offer a unique insight into the multiphase structure of the IGrM and the physical origins of its different components.…”
Section: The Multiphase Igrmmentioning
confidence: 99%
“…Extended O VI distributions of this sort are seen, for example, in simulations of dwarf galaxies (Mina et al 2020). Other possible sources include dwarf galaxies with masses below 10 8 M , quiescent galaxies, galaxy groups and clusters, and the IGM (Prochaska et al 2011;Finn et al 2016;Bielby et al 2019;Burchett et al 2018;Stocke et al 2019).…”
Section: Danforth+2016 Tripp+2008mentioning
confidence: 96%